Accumulation of sadmium and zinc in bottom sediments of different waters of Lithuania - Tautkus Stasys; Steponeniene Laura; Kazlauskas Rolandas (Journal of the Serbian Chemical Society, 2007)
Distribution of cadmium and zinc in the bottom sediments of different waters of Lithuania was investigated using flame atomic absorption spectrometry (FAAS). Two methodologies (liquid and heating mineralization) for the mineralization of the bottom sediments were employed and compared. The accuracy of the FAAS method was evaluated in comparison with a photometric method. The obtained results demonstrate that the suggested procedure could be successfully applied for the analysis of bottom sediments of different water comples with satisfactory accuracy. .